The Miracle of Mosaic Prophecy in The Guide of the Perplexed - Dutmer, Evan (Journal of religious and theological information, 2023)
In this essay, I propose a new interpretative solution to certain difficulties that surround Maimonides’ account of the unique prophecy of Moses described in Exodus, and especially its relation to the general account of prophecy Maimonides develops in The Guide of the Perplexed.I shall argue for an interpretation of the Guide in which Moses’ superiority as a prophet is defended—that is, he does not turn out to be a kind of disguised philosopher—but which nevertheless argues for and reiterates his “intellectual” superiority over the philosophers. To do this, I shall show that while Maimonides relies heavily on Alfarabi’s account of prophecy (which I shall discuss mainly in the context of his The Attainment of Happiness), it is rather in important divergences from Alfarabi and his account that we are able to understand the exceeding specialness of Moses’ prophecy for Maimonides and its implications both for Maimonides’ biblical hermeneutics and political philosophy.